Exposure of Eurasian blackbird (Turdus merula) to Toxoplasma gondii in an urban area in Thuringia, Germany - Mike Heddergott; Rainer Hunold; Natalia Osten-Sacken (International Journal for Parasitology: Parasites and Wildlife)
Toxoplasma gondii is a zoonotic, globally distributed, obligate intracellular protozoan. Within the context of the ‘One Health’ approach, studies on toxoplasmosis are essential as it affects humans as well as domestic and wild animals, including birds. The Eurasian blackbird (Turdus merula) is one of the most common songbird species in Germany and previous studies have shown that they can be infected with T. gondii. The aim of the present study was to analyze T. gondii exposure in an urban blackbird population in Germany. Between 2018 and 2022, we collected fresh blackbird carcasses from an urban population in Heilbad Heiligenstadt, a small town in the German state of Thuringia. Altogether 112 blackbirds were analyzed for the presence of antibodies using a commercial indirect modified agglutination test (MAT) and parasite DNA (qPCR; brain and heart). The present study reports a high T. gondii seroprevalence as antibodies were detected in 50.9 % (57/112; 95 % CI: 41.6–60.2 %) of the urban blackbirds. However, T. gondii DNA was not detected in any of the samples analyzed. Body weight was identified as a risk factor, with heavier birds, both juveniles and adults, being more likely to test positive. Additionally, there was a significant interaction between body weight and sex. Our results suggest that T. gondii infection is widespread in the urban blackbird population, indicating a high parasite circulation in the environment.